Why Rigid Process Management Technology Hampers Computerized Support of Healthcare Processes? - Thom, Lucinéia H.; Reichert, Manfred; Iochpe, Cirano; Oliveira, José Palazzo M. de (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2010: Anais do X Workshop de Informática Médica, 2010)
Healthcare processes are characterized by frequent changes, numerous exceptions and complex deviations from the norm. Despite the increasing adoption of process-aware healthcare information systems (PAHIS), there still exist numerous issues related to the handling of exceptions in clinical processes that are not effectively supported in contemporary PAHIS. This paper presents preliminary results of a research whose goal is to get a deeper understanding of clinical work practices and to better understand how IT process support should look like for them. Altogether, adequate handling of failure and exceptions in PAHIS, while still enabling a certain level of control and assistance to clinical staff.